2009
DOI: 10.1080/07481180902961153
|View full text |Cite
|
Sign up to set email alerts
|

Early Parental Adjustment and Bereavement After Childhood Cancer Death

Abstract: This study comprehensively explored parental bereavement and adjustment at 6 months post-loss due to childhood cancer. Interviews were conducted with 18 mothers and 13 fathers. Interviews were transcribed verbatim and analyzed based on qualitative methodology. A model describing early parental bereavement and adaptation emerged with 3 domains: (1) Perception of the Child, describing bereavement and adjustment prior to and after the loss; (2) Perception of Others, including relationships with partners, survivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
135
0
22

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(176 citation statements)
references
References 42 publications
17
135
0
22
Order By: Relevance
“…These findings mirror research conducted by Bogensperger and Lueger-Schuster (2014), who showed that parents described changed priorities, where work, money and material things were diminished in importance. The same result is described by Barrera, O'Connor, D'Agostino, Spencer, Nicholas, Jovcevska, Tallet and Schneiderman (2009), who stated that bereaved parents change their life views from materialistic things to quality of relationships and place greater importance of the family.…”
Section: Discussionsupporting
confidence: 66%
“…These findings mirror research conducted by Bogensperger and Lueger-Schuster (2014), who showed that parents described changed priorities, where work, money and material things were diminished in importance. The same result is described by Barrera, O'Connor, D'Agostino, Spencer, Nicholas, Jovcevska, Tallet and Schneiderman (2009), who stated that bereaved parents change their life views from materialistic things to quality of relationships and place greater importance of the family.…”
Section: Discussionsupporting
confidence: 66%
“…The data presented here are part of a broader study on the place of death of adolescents and young adults (AYA) with cancer (Montel et al, 2008). This research is the first known parental bereavement study in oncology conducted in France, thereby extending (not just replicating) previous research findings to another country/culture (Barrera et al, 2009;Christ et al, 2003). On the other hand, AYA constitutes a unique group whose bereaved parents may have needs that differ from bereaved parents of younger or older children (Kavanaugh, Trier, & Korzec, 2004).…”
Section: Introductionmentioning
confidence: 79%
“…In adjusting to their loss and moving forward with their lives bereaved parents become emotionally stronger (Bellali & Papadatou, 2006;Buchi, et al, 2007). Their values and priorities are redefined, often finding material things less significant and developing a greater appreciation for family relationships (Armentrout, 2007;Barrera, et al, 2009;Bellali & Papadatou, 2006). In the final phase, many bereaved parents experience personal growth by beginning to find meaning and purpose in their lives.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Bereaved parents who were involved in the decision making surrounding the treatment needs of their child and who felt that their choices to continue in their role of parenting their ill child was respected by health care providers felt confident that they were good parents (Woodgate, 2006). Barrera et al (2009) conducted a longitudinal qualitative study that explored parents adjustment to the death of their child from cancer. Eighteen bereaved mothers and 13 bereaved fathers, including seven couples, participated in the study at 6, 12 and 18 months post-death.…”
Section: Grief In Bereaved Parentsmentioning
confidence: 99%
See 1 more Smart Citation